2017
DOI: 10.1038/s41598-017-12646-3
|View full text |Cite
|
Sign up to set email alerts
|

CCK reduces the food intake mainly through CCK1R in Siberian sturgeon (Acipenser baerii Brandt)

Abstract: To explore the effect of CCK on food intake in Siberian sturgeon, cck cDNA sequence of 1005 bp was obtained, and cck mRNA possessed the highest expression in brain. The expressions of cck were significantly increased after feeding 1 and 3 h, while displaying significant decrease after fasting within 15 days in brain and duodenum. Re-feeding for 3 days induced cck level returned to basic level. Acute i.p. injection experiment showed 100 and 200 ng/g BW CCK8 inhibited the food intake in 0–1 h together with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…The CCKA receptor (CCKAR) has a greater affinity for sulfated than non-sulfated CCK whereas the binding ability of the B receptor (CCKBR) is not affected by sulfation of the tyrosine residue in CCK-8 (Dufresne et al, 2006; Staljanssens et al, 2011). Since the structure of CCK-8 is highly conserved through phylogeny, including fish (Johnsen, 1998; Murashita et al, 2006; Zhang et al, 2017), the commercial sulfated CCK has been used to study the function CCK peptides in appetite regulation and gastrointestinal motility (Olsson et al, 1999; Forgan and Forster, 2007; Tinoco et al, 2015; Zhang et al, 2017). Also, the wrasse CCK-8 has seven out of eight amino acids that are similar to those in human CCK-8 (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CCKA receptor (CCKAR) has a greater affinity for sulfated than non-sulfated CCK whereas the binding ability of the B receptor (CCKBR) is not affected by sulfation of the tyrosine residue in CCK-8 (Dufresne et al, 2006; Staljanssens et al, 2011). Since the structure of CCK-8 is highly conserved through phylogeny, including fish (Johnsen, 1998; Murashita et al, 2006; Zhang et al, 2017), the commercial sulfated CCK has been used to study the function CCK peptides in appetite regulation and gastrointestinal motility (Olsson et al, 1999; Forgan and Forster, 2007; Tinoco et al, 2015; Zhang et al, 2017). Also, the wrasse CCK-8 has seven out of eight amino acids that are similar to those in human CCK-8 (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…In ballan wrasse, we identified five CCK-receptor genes corresponding to CCKAR and CCKBR in other teleosts. CCKAR has been reported to be involved in contractile response of fish intestine (Tinoco et al, 2015; Zhang et al, 2017). The CCKAR has been known to be more involved in digestion than the CCKBR in mammals (Thomas et al, 1979; Dufresne et al, 2006; Staljanssens et al, 2011; Rehfeld, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to these authors, s the administration of Cholecystokinin A (CCKA) receptor antagonists suppressed the effect on satiety. These receptors inhibited the anorect ic effect of exogenous cholecystokinin in rats and mice [36,37]. The increase in satiety caused by simmondsin and that of CCK is generally due to the vague nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Cholecystokinin (CCK), a key hormone in the control of digestion, is released when food is present in the gut in both mammals (e.g., Grider, 1994; Liou et al, 2011; McLaughlin et al, 1998) and fish (e.g., MacDonald and Volkoff, 2009; Pitts and Volkoff, 2017). CCK performs its functions related to gastrointestinal motility and digestion mainly through Cholecystokinin A Receptor (CCKAR) in mammals [reviewed by Staljanssens et al (2011)] and in fish (Tinoco et al, 2015; Zhang et al, 2017). We have previously found that in ballan wrasse, CCK works mainly through CCKA receptors to suppress propulsive contractions, thus prolonging the residence of food in the bulbous for optimal digestion (Le et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%